Medidas morfofuncionais do coração obtidas por ressonância magnética em brasileiros Morphological and functional measurements of the heart obtained by magnetic resonance imaging in Brazilians - Robson Macedo; Juliano Lara Fernandes; Solange Souza Andrade; Carlos Eduardo Rochitte; Kênio Costa Lima; Álvaro Campos Cavalcanti Maciel; Fernanda Cunha Maciel; Geraldo Souza Pinho Alves; Otávio Rizzi Coelho; Rosiane Viana Zuza Diniz (Arquivos Brasileiros de Cardiologia, 2013)
FUNDAMENTO: Medidas ainda hoje utilizadas como referência na ressonância magnética cardíaca foram obtidas principalmente de estudos realizados em populações norte-americanas e europeias. OBJETIVO: Obter medidas do diâmetro diastólico, diâmetro sistólico, volume diastólico final, volume sistólico final, fração de ejeção e massa miocárdica dos ventrículos esquerdo e direito em brasileiros. MÉTODOS: Foram submetidos à ressonância magnética cardíaca, utilizando técnica de precessão livre em estado de equilíbrio, 54 homens e 53 mulheres, com idade média de 43,4 ± 13,1 anos, assintomáticos, sem cardiopatias. RESULTADOS: As médias e os desvios padrão dos parâmetros do ventrículo esquerdo foram: diâmetro diastólico = 4,8 ± 0,5 cm; diâmetro sistólico = 3,0 ± 0,6 cm; volume diastólico final = 128,4 ± 29,6 mL; volume sistólico final = 45,2 ± 16,6 mL; fração de ejeção = 65,5 ± 6,3%; massa = 95,2 ± 30,8 g. Para o ventrículo direito, foram: diâmetro diastólico = 3,9 ± 1,3 cm; diâmetro sistólico = 2,5 ± 0,5 cm; volume diastólico final = 126,5 ± 30,7 mL; volume sistólico final = 53,6 ± 18,4 mL; fração de ejeção = 58,3 ± 8,0% e massa = 26,1 ± 6,1 g. As massas e os volumes foram significativamente maiores nos homens, exceto para o volume sistólico final do ventrículo esquerdo. A fração de ejeção do ventrículo direito foi significativamente maior nas mulheres. Houve correlação significativa e inversa do volume sistólico do volume direito com o aumento da idade. CONCLUSÃO: Este estudo descreveu, pela primeira vez, medidas cardíacas obtidas pela ressonância magnética cardíaca em brasileiros assintomáticos, sem cardiopatias, mostrando diferenças de acordo com o gênero e a idade. BACKGROUND: Still today, measurements used as a reference in the cardiac magnetic resonance imaging have been obtained mainly from studies carried out in North-American and European populations. OBJECTIVE: To obtain measurements of the diastolic diameter, systolic diameter, end diastolic volume, end systolic volume, ejection fraction, and myocardial mass of the left and right ventricles in Brazilians. METHODS: 54 men and 53 women, with mean age of 43.4 ± 13.1 years, asymptomatic, with no cardiomyopathies, have been subjected to the cardiac magnetic resonance imaging, using a balanced steady state free precession technique. RESULTS: The averages and the standard deviations of the parameters for the left ventricle have been: diastolic diameter = 4.8 ± 0.5 cm; systolic diameter = 3.0 ± 0.6 cm; end diastolic volume = 128.4 ± 29.6 mL; end systolic volume = 45.2 ± 16.6 mL; ejection fraction = 65.5 ± 6.3%; mass = 95.2 ± 30.8 g. For the right ventricle, they have been: diastolic diameter = 3.9 ± 1.3 cm; systolic diameter = 2.5 ± 0.5 cm; end diastolic volume = 126.5 ± 30.7 mL; end systolic volume = 53.6 ± 18.4 mL; ejection fraction = 58.3 ± 8.0%, and mass = 26.1 ± 6.1 g. The masses and the volumes were significantly greater in the men, except for the end systolic volume of the left ventricle. The ejection fraction of the right ventricle has been significantly greater in the women. There has been a significant and inverted correlation of the systolic volume of the right volume with the progression of the age. CONCLUSION: This study has described, for the first time, cardiac measurements obtained through the cardiac magnetic resonance imaging in Brazilians, asymptomatic, with no cardiomyopathies, showing differences in accordance with gender and age.